Studi Etnobotani Tumbuhan Obat oleh Masyarakat Perkebunan Kelapa Sawit dalam Mendukung Pengelolaan Perkebunan yang Berkelanjutan (Studi Kasus di Perkebunan PT. Unggul Widya Teknologi Lestari) - Aang Kuvaini; . Yuliyanto; . Bahtiar (Politeknik Kelapa Sawit Citra Widya Edukasi, 2020)
The existence of weeds in oil palm plantations is considered very detrimental and even has no benefit at all. However, it turns out that there are several weeds in oil palm plantations that can be used, one of which is a medicinal plant. Some of these weed species are considered by the plantation community as an alternative to making traditional medicines considering that the oil palm plantation areas are very far from pharmaceutical centers. This research was conducted at the oil palm plantation of PT Unggul Widya Teknolgi Lestari, Pasangkayu Regency, West Sulawesi, in March-June 2020. The purpose of this study was to determine the types and methods of processing weeds as traditional medicines by the oil palm plantation community. The methods used in this research are field observations, in-depth interviews with key informants from community elements and oil palm plantation managers. Qualitative descriptive analysis is used to explain the results of surveys and interviews systematically which is strengthened by literature study. Based on the results of the study showed that in the oil palm plantation PT Unggul Widya Teknologi Lestari, there are 10 weed plants which are commonly used by plantation communities as traditional medicine. The processing method includes the boiling method and using it directly. The use of weed plants as traditional medicine also contributes to efforts to control weeds in an environmentally friendly and sustainable manner in oil palm plantations.